First Cultivation of Health-Associated Tannerella sp. HOT-286 (BU063). (October 2016) - Vartoukian, S.R.; Moazzez, R.V.; Paster, B.J.; Dewhirst, F.E.; Wade, W.G.
Despite significant advances in recent years in culture-independent molecular microbiology methods, the detailed study of individual bacterial species still relies on having pure cultures in the laboratory. Yet, more than a third of the approximately 700 bacterial taxa found in the human oral cavity are as yet uncultivated in vitro. One such taxon, Tannerella sp. HOT-286 (phylotype BU063), is the focus of much interest since it is associated with periodontal health, while Tannerella forsythia, its closest phylogenetic neighbor, is strongly associated with periodontal disease. HOT-286, however, has remained uncultivated despite the efforts of several research groups, spanning over a decade. The aim of this study was to cultivate Tannerella sp. HOT-286. A heavily diluted sample of subgingival plaque was inoculated onto culture plates supplemented with siderophores (pyoverdines-Fe complex or desferricoprogen) or a neat plaque suspension. After 8 d of anaerobic incubation, microcolonies and colonies showing satellitism were passaged onto fresh culture plates cross-streaked with potential helper strains or onto cellulose-acetate membranes placed over lawn cultures of helper strains. Subcultured colonies were identified by 16S rRNA gene sequencing, and purity was confirmed by sequencing 20 clones per library prepared from a single colony. Three colonies of interest (derived from pyoverdines- and plaque-supplemented plates) were identified as Tannerella sp. HOT-286. The isolates were found to be incapable of independent growth, requiring helpers such as Propionibacterium acnes and Prevotella intermedia for stimulation, with best growth on membranes over "helper" lawns. A representative isolate was subjected to phenotypic characterization and found to produce a range of glycosidic and proteolytic enzymes. Further comparison of this novel "periodontal health-associated" taxon with T. forsythia will be valuable in investigating virulence factors of the latter and possible health benefits of the former.